Blended Learning in a Higher Education Context: Exploring University Students' Learning Behavior - Kleopatra Nikolopoulou; Georgios Zacharis (MDPI AG, 2023)
Blended learning is a growing phenomenon in higher education after the COVID-19 pandemic (the educational process moved entirely online), and the way is prepared for blended education mode in universities. Although blended learning research is on the rise, fewer studies regard university students' learning behavior in blended learning environments. This study aims to investigate university students' blended learning behavior perceptions shortly after the pandemic. A 19-item questionnaire was administered to 176 university students in Greece. Students, in general, expressed positive blended learning behavior perceptions. Higher percentages of agreement were associated with the role of audio-visual online resources in facilitating and supporting independent learning and with student motivation in blended education. Students expressed lower percentages of agreement, and some uncertainty, with regard to involvement in small group work with their peers. Implications for students, educators, as well as university policy and practice are discussed.